2023
DOI: 10.1063/5.0145826
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-induced 2D electron gases in N-polar AlGaN/AlN heterostructures on single-crystal AlN substrates

Abstract: Polarization-induced carriers play an important role in achieving high electrical conductivity in ultrawide bandgap semiconductor AlGaN, which is essential for various applications ranging from radio frequency and power electronics to deep UV photonics. Despite significant scientific and technological interest, studies on polarization-induced carriers in N-polar AlGaN are rare. We report the observation and properties of polarization-induced two-dimensional electron gases (2DEGs) in N-polar AlGaN/AlN heterostr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Ga 2 O 3 possesses five polymorphs, specifically α, β, γ, δ, and ε. Among these, the ε-phase is noted for its remarkable polarization property, which is an order of magnitude greater than GaN, a semiconductor material typically employed in high electron mobility transistors (HEMTs). , The findings on polarization of ε-phase Ga 2 O 3 have piqued the interest of numerous researchers that are exploring the possibilities of ε-Ga 2 O 3 based devices. Chen et al have reported on the polarization switching properties of κ-Ga 2 O 3 (where κ and ε denote the same phase of Ga 2 O 3 ) in κ-Ga 2 O 3 /GaN heterostructure, revealing a remanent polarization of approximately 2.7 μC/cm 2 . Wang et al have indicated that the interface of ε-Ga 2 O 3 / m -GaN ( m -AlN) could achieve a high two-dimensional electron gas (2DEG) density of 10 14 cm –2 .…”
Section: Introductionmentioning
confidence: 99%
“…Ga 2 O 3 possesses five polymorphs, specifically α, β, γ, δ, and ε. Among these, the ε-phase is noted for its remarkable polarization property, which is an order of magnitude greater than GaN, a semiconductor material typically employed in high electron mobility transistors (HEMTs). , The findings on polarization of ε-phase Ga 2 O 3 have piqued the interest of numerous researchers that are exploring the possibilities of ε-Ga 2 O 3 based devices. Chen et al have reported on the polarization switching properties of κ-Ga 2 O 3 (where κ and ε denote the same phase of Ga 2 O 3 ) in κ-Ga 2 O 3 /GaN heterostructure, revealing a remanent polarization of approximately 2.7 μC/cm 2 . Wang et al have indicated that the interface of ε-Ga 2 O 3 / m -GaN ( m -AlN) could achieve a high two-dimensional electron gas (2DEG) density of 10 14 cm –2 .…”
Section: Introductionmentioning
confidence: 99%